The Solution of Group Behavior as a Model for Improving Human Resources in the Public Sector - Romanda Annas Amrullah (Soegijapranata Catholic University, 2021)
Public sector human resources, more widely known as civil servants (PNS) are of particular concern to various ministries and the general public, due to their involvement in political activities, and despicable actions to radicalism activities, civil servants should be able to become role model for the community due to their status as state servants this is based on the rules that apply to the ASN code of ethics. Unfortunately, this is counterproductive to their function and role as public services. This research aims to find out what causes civil servants easily influenced by radical actions and provide solutions for how to prevent this. This research used descriptive qualitative methods to describe a social phenomenon happening right now. The results showed that the public sector resources involved in political activities committed despicable acts to be exposed to radicalism for providing wrong information as we already know that in 2019 There are at least five ASN suspected of being exposed to radicalism. Integrating the theory of selective exposure, the theory of identity, and social transmission. This research resulted in the concept of a novel model of Isolation Group Behavior (private selective, Internal Radicalism Prevention for States Civil Servants or ASN with Selective Information). The application of isolation group behavior can improve human resources in the public sector so they become role models for public society